Madame Cora Millet-Robinet - Jaine, Tom (Petits Propos Culinaires, 2015)
The author provides some observations about his recent work  translating the first volume of the fourth edition of Cora Millet-Robinet’s Maison rustique des dames, published in two volumes by the Librairie agricole de la Maison rustique in 1859 and provides a translation of the opening section of that book in which Millet-Robinet offers advice to country housewives of the time.